Assessing Ghana's Contemporary Tourism Development Experience - Kwaku Adutwum Boakye; Ferdinand Otibo; Foster Frempong (Journal of Global Initiatives, 2013)
The re-emerging acceptance of tourism as a pathway to development has culminated in widespread adoption of the trade by many poor countries. Ghana is one such country and, over the past three decades, has sought to use tourism as means of diversifying its econ-omy. The substantial amounts invested in tourism by the government make it imperative to continually evaluate tourism performance and outcomes as a tool for socio-economic development. Yet, to date, very few studies have placed Ghana’s tourism experience un-der the spotlight. This paper focuses on how the trade has evolved into a major economic activity. It assesses the country’s interventions in the tourist trade over the years and it examines the performance of the tourist trade, first as an economic activity and second within its expected role as an agent for overall human development. By and large, the findings suggest that Ghana’s tourism development experience has been characterized by mixed fortunes. While there are indications of impressive macroeconomic gains, there have been challenges in the quest to translate these into the expected developmental out-comes at the more disaggregated communal and individual levels. Some weaknesses, no-tably, defects in policy, a powerless public sector, and low human capacities are suggest-ed as contributing to the current state of stagnation the sector is experiencing.